PERANCANGAN SISTEM INFORMASI PURCHASE ORDER BERBASIS WEB PADA CV STARK ENGINEERING INDONESIA - Fawwazy , Neyzard Alby; Donoriyanto, Dwi Sukma (Tekmapro, 2024)
An information system is a series of components that work together with each other to collect, process, store, and disseminate information to support decision making, coordination, and control of an organization. CV Stark Engineering Indonesia is a company that distributes hot runner spare parts (plastic molding machines) which has been established since 2018. Every day this company carries out quite large transaction activities. However, so far, the recording of sales and purchase transactions is still done manually using Word and Excel applications. This then often becomes a problem due to the recording of Purchase Order (PO) numbers being duplicated between each other.